INFLUENCE OF THICK EXTRACT FROM MAITAKE MUSHROOMS ON SIGNS OF INFLAMMATORY PROCESS IN EXPERIMENTAL TOXIC HEPATITIS - Herasymets, I. I.; Fira, L. S.; Medvid, I. I. (International Journal of Medicine and Medical Research, 2021)
Background. The priority of the contemporary pharmaceutical industry is to create effective, safe and inexpensive drugs to ensure the highest quality of care and optimal use of available raw materials. Objective. The aim of our study was to investigate anti-inflammatory properties of the Maitake mushrooms thick extract in the experiment on rats with paracetamol(acetaminophen)-induced hepatitis. Methods. 60 white male rats, weighing 180-210 g, randomized into 10 groups of 6 animals in each, were used for the experiment. Paracetamol hepatitis was simulated by acetaminophen intragastric administering in a dose of 1250 mg/kg 1 time per day (for 2 days) as a suspension in 2% starch gel solution. Maitake mushrooms thick extract, which was administered intragastrically 2 hours before the administration of acetaminophen and daily after the lesion in a dose of 150 mg/kg of the animal’s body weight, was used for the toxic lesion correction. “Silibor” was selected as the comparison drug, which was administered according to the same scheme as the investigated extract in a dose of 20 mg/kg of the animal’s body weight. Euthanasia was conducted on the 3rd, 7th and 10th day of the experiment with sodium barbamyl. Liver homogenate and animal serum were used for the studies. The development of inflammatory processes was studied by the content of pro-inflammatory and anti-inflammatory cytokines, as well as C-reactive protein in the serum of rats with toxic hepatitis and after the application of Maitake mushroom extract and the comparison drug. Results. It was found that the introduction of acetaminophen to animals for the acute hepatitis simulation is accompanied by changes in the cytokine profile, i.e. an increase in the level of IL-6 and a decrease in the level of IL-4 in the serum of rats. Inflammatory development is evidenced by the content of C-reactive protein increase in the blood of the affected animals. The application of Maitake mushroom extract facilitated bringing the studied indicators almost to the level of intact control. Conclusions. Reduction of inflammation signs in rats with the simulated paracetamol hepatitis under the influence of Maitake mushrooms thick extract confirms its anti-inflammatory properties. Objective. The aim of our study was to investigate anti-inflammatory properties of the Maitake mushrooms thick extract in the experiment on rats with paracetamol(acetaminophen)-induced hepatitis. Methods. 60 white male rats, weighing 180-210 g, randomized into 10 groups of 6 animals each, were used for the experiment. Paracetamol hepatitis was simulated by acetaminophen intragastric administering in a dose of 1250 mg/kg 1 time per day (for 2 days) as a suspension in 2% starch gel solution. Maitake mushrooms thick extract, which was administered intragastrically 2 hours before the administration of acetaminophen and daily after the lesion in a dose of 150 mg/kg of the animal’s body weight, was used for the toxic lesion correction. "Silibor" was selected as the comparison drug, which was administered according to the same scheme like the investigated extract in a dose of 20 mg/kg of the animal’s body weight. Euthanasia was conducted on the 3rd, 7th and 10th day of the experiment with sodium barbamyl using. Liver homogenate and animal serum were used for the studies. The development of inflammatory processes was studied by the content of pro- and anti-inflammatory cytokines, as well as C-reactive protein in the serum of rats with toxic hepatitis and after the application of Maitake mushroom extract and the comparison drug. Results. It was found that the introduction of acetaminophen to animals for the acute hepatitis simulation is accompanied by changes in the cytokine profile, namely, an increase in the level of IL-6 and a decrease in the level of IL-4 in the serum of rats. The inflammatory process development is evidenced by the content of C-reactive protein increasing in the blood of affected animals. The application of Maitake mushroom extract helped to bring the studied indicators closer to the level of intact control. Conclusions. The application of the Maitake mushrooms thick extract as a corrective factor at the simulated paracetamol hepatitis confirms its anti-inflammatory properties. KEYWORDS: Maitake mushrooms, paracetamol, hepatitis, inflammatory processes, thick extract, anti-inflammatory properties.